Network approach reveals preferential T-cell and macrophage association with α-linked β-cells in early stage of insulitis in NOD mice - Balasenthilkumaran, Nirmala V.; Whitesell, Jennifer C.; Pyle, Laura; Friedman, Rachel S.; Kravets, Vira (Frontiers in Network Physiology, 2024)
One of the challenges in studying islet inflammation -insulitis -is that it is a transient phenomenon.Traditional reporting of the insulitis progression is based on cumulative, donor-averaged values of leucocyte density in the vicinity of pancreatic islets, that hinder intra-and inter-islet heterogeneity of disease progression. Here, we aimed to understand why insulitis is non-uniform, often with periinsulitis lesions formed on one side of an islet. To achieve this, we demonstrated the applicability of network theory in detangling intra-islet multi-cellular interactions during insulitis. Specifically, we asked the question "What is unique about regions of the islet that interact with immune cells first". This study utilized the non-obese diabetic mouse model of type one diabetes and examined the interplay among α-, β-, T-cells, myeloid cells, and macrophages in pancreatic islets during the progression of insulitis. Disease evolution was tracked based on the T/b cell ratio in individual islets. In the early stage, we found that immune cells are preferentially interacting with α-cell-rich regions of an islet. At the islet periphery α-linked β-cells were found to be targeted significantly more compared to those without α-cell neighbors. Additionally, network analysis revealed increased T-myeloid, and T-macrophage interactions with all b-cells.